The Impact of Remittances on Albanian GDP and Houshold Income Level - Manushi, Besije (Richtmann Publishing, 2012)
After the fall of communist regime or from the beginning of the 1990’s, Albania is one of the countries with the large number ofemigrants, and it is one of the country that mostly receives remittances which are funds received from migrants working abroad. The aimof this paper is to show the impact of remittances on the Albanian economy and the effect that it has in the GDP and the economicgrowth. Also, this paper is going to analyze the impact of remittances on poverty level in Albania. Studies show that remittances have asignificant impact on the reduction of poverty in the country by directly raising household income and consumption .It is going to be usedthe regression analysis with the data received from INSTAT and World Bank in order to have a more clear information about the impactof the remittances in Albania economy and on the household income level of people. At the end of the analysis it is going to bediscussed the conclusions the importance of remittances, if they play a key role in economy.